Streaming the past : peninsular India in history : essay in honour of T.K. Venkatasubramanian - Venkatasubramanian, T. K.; Sarkar, Nilanjan; Verma, Vikas K. (Delhi : Primus Books, 2019)
Contributed articles.
Includes bibliographical references and index.
Keywords: Tamil Nadu (India) -- History; Tamil Nadu (India) -- Antiquities; India, South -- History